2021
DOI: 10.1002/pen.25811
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in situ fibrillation on polyethylene/poly(ethylene terephthalate)/multiwalled carbon nanotube electromagnetic shielding foams

Abstract: In this study, polyethylene (PP)/polyethylene terephthalate (PET)/multiwalled carbon nanotube (MWCNT) nanocomposites with nanofibrillary structure were processed by hot drawing‐assisted extrusion technology, and nonfoaming and microfoaming samples were processed by injection molding machine. Scanning electron microscope micrographs showed that when PET content was 2.5 wt%, PET fibers had a larger aspect ratio, which brought an outstanding promotion on microfoaming of PP matrix, and further details were provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…The melt heat absorption peaks of the PP/MWCNTs binary composite and the PP/MWCNTs/PTFE multicomposite also moved to higher temperatures after the second melt heat absorption process, which may be related to some crystal structures becoming more perfect. 16,18 Table 4 summarizes the key parameters of nonisothermal thermal crystallinity of the component materials. It was found that for the PC1 and PC2 groups, the crystallinity decreased with the addition of MWCNTs over pure PP.…”
Section: Crystallization Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The melt heat absorption peaks of the PP/MWCNTs binary composite and the PP/MWCNTs/PTFE multicomposite also moved to higher temperatures after the second melt heat absorption process, which may be related to some crystal structures becoming more perfect. 16,18 Table 4 summarizes the key parameters of nonisothermal thermal crystallinity of the component materials. It was found that for the PC1 and PC2 groups, the crystallinity decreased with the addition of MWCNTs over pure PP.…”
Section: Crystallization Behaviormentioning
confidence: 99%
“…14,15 Most previous studies have focused on in situ fibrillation-based method for obtaining fibrils with high aspect ratios, which is increasingly recognized as an effective method to improve melt strength, rheology properties, and foaming behavior. [16][17][18][19] Furthermore, the presence of fibrillar networks is related to the role of heterogeneous nucleation agents in refining crystals. Jiang et al 20 introduced polytetrafluoroethylene (PTFE) fibrils into the prepared microporous polyethylene terephthalate (PET), which improved the crystallization temperature, crystallization rate, as well as the viscoelastic behavior of PET.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Carbon-based wave absorbers include carbon black, graphene, graphene oxide (GO), carbon fibers, carbon nanotubes (CNTs), and so forth. [13][14][15] There are many studies on polymer-based electromagnetic wave absorbing porous nanocomposites with carbon-based absorbers. Zhang et al [16] prepared polyurethane/GO composite foams by impregnation, and the results showed that the reflection loss of the foam with a density of 0.027 g/cm 3 can reach À46.2 dB as the addition amount of GO was 30%.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-walled CNTs (MWCNTs) have been extensively used as reinforcements due to their relatively low cost and easy availability. [31][32][33][34][35][36][37][38][39][40][41][42] However, a minimal study has been done on singlewalled CNTs (SWCNTs), [43][44][45][46][47][48][49] whereas there is almost no work to date on SWCNT reinforced flexible ethylene methyl acrylate (EMA) polymer matrix nanocomposites.…”
Section: Introductionmentioning
confidence: 99%